2013
DOI: 10.1142/s0218127413501356
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Memory Element and Chaotic Memory System

Abstract: The concept of memory element or memory system is generalized to any device or system with memory effect in this paper. With the general definition of memory element, a new memory element model is proposed and its properties are studied. Based on the memory element, a simple chaotic memory system is constructed and its complex dynamics is depicted. These results verified by circuit experimental observations and PSIM simulations indicate that the proposed memory element has a pinched hysteresis loop characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…It is worth noting that the stability depends on the memristor initial condition in a memristive dynamical circuit, leading to the occurrence of coexisting multiple attractors [9,13]. The coexistence of different kinds of attractors, called multistability, reveals a rich diversity of stable states in nonlinear dynamical systems [12,[24][25][26][27][28][29][30][31][32] and makes the system offer great flexibility, which can be used for image processing or taken as an additional source of randomness used for many information engineering applications [32][33][34][35][36][37]. Therefore, it is very attractive to seek for a simple memristive chaotic circuit that has the striking dynamical behavior of coexisting multiple attractors.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the stability depends on the memristor initial condition in a memristive dynamical circuit, leading to the occurrence of coexisting multiple attractors [9,13]. The coexistence of different kinds of attractors, called multistability, reveals a rich diversity of stable states in nonlinear dynamical systems [12,[24][25][26][27][28][29][30][31][32] and makes the system offer great flexibility, which can be used for image processing or taken as an additional source of randomness used for many information engineering applications [32][33][34][35][36][37]. Therefore, it is very attractive to seek for a simple memristive chaotic circuit that has the striking dynamical behavior of coexisting multiple attractors.…”
Section: Introductionmentioning
confidence: 99%
“…By extending the definition of the memristive system [2,[19][20][21], we introduce a generalized memristive device, depicted by the following relation:…”
Section: Generalized Memristive Devicementioning
confidence: 99%
“…Figure 1 From the simulation results in Figures 1 and 2, it can be seen that the memory device is not passive and behaves as a linear negative commutator in the limit of infinite frequency. Besides, there exist at most two values of the output r t for any designated input y t [20]. 2 Complexity…”
Section: Generalized Memristive Devicementioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26] In 1993, Stone and Miranda observed first multiwing chaotic attractor from a proto-Lorenz system. 4-12 Since the mathematical model involving chaos was first suggested by Lorenz 13 in 1963 and the term chaos was first used by Li and Yorke 14 in 1975, the design of new chaotic systems with complex topological structures are attracting more and more interest in the research.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Since the mathematical model involving chaos was first suggested by Lorenz 13 in 1963 and the term chaos was first used by Li and Yorke 14 in 1975, the design of new chaotic systems with complex topological structures are attracting more and more interest in the research. [15][16][17][18][19][20][21][22][23][24][25][26] In 1993, Stone and Miranda observed first multiwing chaotic attractor from a proto-Lorenz system. 27 Since then, people has found that a wide variety of memristor-based systems can exhibit the complicated dynamics, particularly in birth of multiwing attractors.…”
mentioning
confidence: 99%